Early‐life antibiotic exposure increases the risk of developing allergic symptoms later in life: A meta‐analysis. Issue 5 (28th November 2017) - Ahmadizar, F.; Vijverberg, S. J. H.; Arets, H. G. M.; de Boer, A.; Lang, J. E.; Garssen, J.; Kraneveld, A.; Maitland‐van der Zee, A. H.
Abstract: This study systematically reviewed and quantified the relationship between exposure to antibiotics during the first 2 years of life and the risk of allergies/atopies including hay fever, eczema, food allergy, positive skin prick testing (SPT), or elevated allergen‐specific serum/plasma immunoglobulin (Ig) E levels later in life. PubMed and Web of Science databases were searched for observational studies published from January 1966 through November 11, 2015. Overall pooled estimates of the odds ratios (ORs) were obtained using fixed or random‐effects models. Early‐life exposure to antibiotics appears to be related to an increased risk of allergic symptoms of hay fever, eczema, and food allergy later in life. The summary OR for the risk of hay fever (22 studies) was 1.23, 95% confidence interval (CI):1.13‐1.34; I 2 : 77.0%. The summary OR for the risk of eczema (22 studies) was 1.26, 95% CI: 1.15‐1.37; I 2 : 74.2%, and the summary OR for food allergy (3 studies) was 1.42, 95% CI: 1.08‐1.87; I 2 : 80.8%. However, no association was found for antibiotics exposure early in life and objective atopy measurements including positive SPT or elevated allergen‐specific serum/plasma IgE levels. Abstract :